LAS PROPIEDADES EDÁFICAS EN LA DETERMINACIÓN DEL ÍNDICE DE SITIO PARA DOS ESPECIES DE PINO EN URUAPAN, MICHOACÁN - Madrigal H., Salvador; Ranúrez M., Hugo (Revista Mexicana de Ciencias Forestales, 2020)
A soil sampling was made in the Campo Experimental Barranca de Cupatitzio, that is located near Uruapan City, State of Michoacan, Mexico, to relate soil variables with site index for Pinus douglasiana Martínez and P. lawsonii Roezl. The soil sample was taken from 28 soil profiles with two thinkness horizons: A and AC. The properties and characteristics percentage of sand, clay and silt, apparent density, available moisture, pH, phosphorus, nitrates, etc. were taken as independent variables. The independent variables selection was made according as a contribution to explain the site index variability, this is its contribution to R2, by means of the STEPWISE procedure of SAS computer package. The results shown that for P douglasiana the site index variability is explainable mainly by the apparent density and the avialable water lamina, also, by the available water lamina and the porous space with average values by profile. Whereas for P lawsonii only the apparent density in the horizon A explain the Site Index variability.